Nos palcos da história: teatro, política e liberdade, liberdade (1965-1967) - Natalia Cristina Batista (2013)
Freedom, freedom, authored by Flávio Rangel and Millôr Fernandes will be the object of appreciation of this work. Its aim will be to analyze the spectacle produced by Group Opinion and starring Paulo Autran, considering the politicals and artistic questions, that overpassed his career. Although the staging is the central point of the research, we intend to analyze cultural products derived from the spectacle, namely: the book, edited by Brazilian Civilization, the record, released by Forma Records and the Sambas Contest, about freedom, organized by producers of the spectacle. In order to insert these cultural products in the Brazilian artistic quotidian, we aimed to analyze how it processed the relation between theatre and politics, between art and power. The dramaturgical text Freedom, freedom, was intended to protest against the Brazilian Military Dictatorship, but to avoid a direct confrontation with the Military regime, it was built through several historical events that talked about freedom or showed periods of history where men had the freedom curtailed. To understand the scope of this objective in the spectacle and its cultural products, we will mobilize its insertion into a left-wing political culture, also investigating the trajectory of the Group Opinion, the creators of the play, the cast, the producers, as well the relations established with the government, the criticism, the public and the media censorship. It was observed in Freedom, Freedom the existence of an unequal dialogue between the play and the military regime, as several contradictions in the form of engagement required by the play and in its repercussion.